The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/smj.3240
|View full text |Cite
|
Sign up to set email alerts
|

Out of character: CEO political ideology, peer influence, and adoption of CSR executive position by Fortune 500 firms

Abstract: Research Summary We consider the link between firms' decisions to adopt a CSR executive position and the political ideology of prior adopter CEOs. We theorize that firms are more likely to adopt a CSR executive position when it has been previously adopted by conservative‐leaning CEOs at other firms, as opposed to liberal‐leaning CEOs. This effect is due, we argue, to the increased perceptual salience and situational attributions associated with ideologically incongruent actions (i.e., actions that appear incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 101 publications
0
54
1
Order By: Relevance
“…The earliest in the use of distance learning were corporate universities, once again proving their flexibility and superiority over traditional educational institutions. A Web-based learning project, launched by 500 Fortune corporations in the United States, Gupta et al (2021), has been confirmed for the following benefits of "virtual" CU:  Significant cost reduction (there is no need to rent space for classrooms and organize travel / accommodation for students).  All tasks, as well as participation in seminars and listening to lectures, are performed at their workplace or in the evening at home, after work.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest in the use of distance learning were corporate universities, once again proving their flexibility and superiority over traditional educational institutions. A Web-based learning project, launched by 500 Fortune corporations in the United States, Gupta et al (2021), has been confirmed for the following benefits of "virtual" CU:  Significant cost reduction (there is no need to rent space for classrooms and organize travel / accommodation for students).  All tasks, as well as participation in seminars and listening to lectures, are performed at their workplace or in the evening at home, after work.…”
Section: Resultsmentioning
confidence: 99%
“…A growing literature in strategic management examining the influence of decision makers' ideologies on firm outcomes shows that while conservatives view their responsibility towards shareholders as primary, liberals consider a broader range of stakeholder needs as relevant to the goals of the firm (Chin et al, 2013). Accordingly, there is a robust relationship between liberalism and CSR activities at both the top management and board level (Chin et al, 2013;di Giuli & Kostovetsky, 2014;Gupta et al, 2020), while conservative managers have been associated with higher financial performance (Hutton et al, 2014). More recently, the marketing literature has begun to explore the antecedents and consequences of corporate sociopolitical activism, where firms take a public stance on divisive political or social issues (Bhagwat et al, 2020).…”
Section: Homophily In Intra-and Inter-organizational Networkmentioning
confidence: 99%
“…Most research to date has examined situational factors, leading to a theoretical understanding of board composition and network formation that may understate the role of directors' cognitive and affective frames (Gupta & Wowak, 2017; Shropshire, 2010), despite longstanding recognition that the values, beliefs, and attitudes of decision makers affect firm‐level outcomes (Chin et al, 2013). Research on top management teams (TMTs) (Chin et al, 2013; Chin & Semadeni, 2017; Christensen et al, 2015; Gupta et al, 2020; Hutton et al, 2014; Kashmiri & Mahajan, 2017), and some notable exceptions to the situational focus in board research (di Giuli & Kostovetsky, 2014; Gupta & Wowak, 2017; Park et al, 2020), highlight a key dispositional factor: ideology . This refers to an individual's internally consistent belief system, comprising the attitudes and values that underlie thought and behavior (Jost, 2006; Tedin, 1987), and is observable and measurable by political orientations (Chin et al, 2013; Erikson & Tedin, 2003; Jost et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations